Back Cover: Dietary EPA‐Enriched Phospholipids Alleviate Chronic Stress and LPS‐Induced Depression‐ and Anxiety‐Like Behavior by Regulating Immunity and Neuroinflammation. Issue 17 (2nd September 2021) - Wang, Cheng‐Cheng; Du, Lei; Shi, Hao‐Hao; Ding, Lin; Yanagita, Teruyoshi; Xue, Chang‐Hu; Wang, Yu‐Ming; Zhang, Tian‐Tian
Abstract : Mol. Nutr. Food Res . 2021, 65, 202100009 DOI: 10.1002/mnfr.202100009 Dietary eicosapentaenoic acid enriched phospholipids (EPA‐PL) exhibit significant effects on alleviating depression‐ and anxiety‐like behavior, and the possible underlying mechanisms may be involved in regulating immunity and neuroinflammation, increasing monoamine neurotransmitters, and regulating hypothalamic‐pituitary‐adrenal (HPA) axis. This is reported by Tian‐Tian Zhang and co‐workers in article number 2100009 .